Effect of acidosis on bilirubin-induced toxicity to human erythrocytes - Brito, MA (2015)
Unconjugated bilirubin binds to erythrocytes, eliciting crenation, lipid elution and hemolysis. The present work attempts to establish the role of acidosis on bilirubin-induced toxicity to human erythrocytes. To this end, pH values ranging from 7.0-8.0 we